EFFECT OF STORAGE TIME VARIATION OF ANDALIMAN FRUIT ON FREE RADICAL SCAVENGING AND PROLIFERATION INHIBITION ON MCF-7 CELLS - Rosidah, Idah; Kusumastuti, Siska Andrina; Simanungkalit, Grace Sophiwati; Rahayu, Maya Damayanti; Nuralih, Nuralih; Martgrita, Merry Meryam; Kembaren, Roga Florida; Chaidir, Chaidir; Sunaryanto, Rofiq; Wibowo, Agung Eru (BRIN Publishing (Penerbit BRIN), 2024)
Andaliman (Zanthoxylum acanthopodium D.C) is a plant widely used by the Batak people in North Sumatera. Several studies demonstrated that Andaliman fruit exhibits antioxidant activities and cytotoxic effects on cancer cells. Quality of Andaliman fruit could affected by post-harvest process including storage time. This research aims to analyze the compound, antioxidant activity and proliferation inhibition on MCF-7 cells of Andaliman fruit extracts (AFE) stored at varying storage time. A series of fresh 250 g Andaliman fruit sealed in a closed container and stored in the oven at 30ºC. After storage at 0, 24, 48, 72, 96, 120 and 144 hours, Andaliman fruit macerated using methanol and obtained successive extract yields of 4.12; 3.70; 12.79; 8.17; 8.15; 3.7 and 2.21. These extracts were analyzed for total phenolic, total flavonoids, free radical scavenging activity and proliferation inhibition on MCF-7 cells. The chemical compound analysis of AFE was performed by ultra performance liquid chromatography (UPLC). Results showed that the AFE stored at zero hours had higher total phenol content (47.32 mg gallic acid equivalent (GAE)/g of extract) and free radical scavenging activity (50.38%) at 500 µg/mL significantly compared to other extracts. The total flavonoid content of all extracts showed no difference level except for the extract at 120 hours of storage. The proliferation inhibition test on MCF-7 cells at 100 µg/mL showed that AFE stored at 72, 96 and 144 hours could inhibit MCF-7 cells above 50%. The storage time variation of Andaliman fruit may affect the total phenolic and flavonoid content, and also activity of free radical scavenging and proliferation inhibition on MCF-7. The UPLC analysis founded the major compound of AFE was predicted as α-sanshool. Analysis of chemicals substance in Andaliman fruit with varying of storage time need to be conducted to evaluated alteration of secondary metabolites contained in Andaliman fruit.